CULTURAL DIVERSITY IN ENGLISH-SPEAKING COUNTRIES - Khalilova Shokhista Mukhammadi qizi,; Rashidova Gulchekhra Olimjon qizi, (TADQIQOTLAR, 2026)
Abstract This  article  analyzes  cultural  diversity  in  English-speaking  countries  from historical,  sociolinguistic,  and  intercultural  perspectives.  The  research  examines multiculturalism, national traditions, educational systems, and cultural interaction in countries such as the United States, the United Kingdom, Canada, Australia, and New Zealand.  The  study  highlights  the  importance  of  intercultural  communication  and linguistic diversity in the modern globalized world.